Distribución espacio-temporal de la biomasa fitoplánctica en el sistema lagunar Pom-Atasta, Campeche, México - Barreiro-Güemes, Ma. Teresa; Aguirre-León, Arturo (Revista de Biología Tropical, 1999)
Spatial and temporal patterns of concentration of chlorophyll a as an indicator of phytoplanktic biomass were evaluated in Pom-Atasta, a fluvial-deltaic system linked to Terminos Lagoon in the Campeche coast, Mexico. The seasonal, regional, nichthemeral and vertical variation patterns were studied and related with environmental conditions. An annual cycle was analyzed in the system, including sampling at two water levels (surface and bottom) in constrasting sites by their saline regime. Time series of 24 hours were performed in sites with more hydrological variation. Spectrophotometric technics were used to quantify the concentration of chlorophyll a. The highest concentrations were present during the dry season with an average of 19.86 mg m-3, and the lowest concentrations were during the rainy season with an average of 3 mg m-3. The total mean in the annual cycle was 13.25 mg m-3 in the surface and 15.5 mg m-3 in the bottom. Regional pattern in pigment concentrations was observed, with the highest values in the site of lower tide influence. A great range of variation in chlorophyll concentrations was evident within the annual cycle and in different regions of the system. This patterns of variation seems to be closely related with the hydrological changes resulting of the input balance of tidal waters, rainfall and fresh water discharges.